Analysis of 5C+1S Principles in Minimizing the Risk of Working Capital Murabahah Financing - Hadratullah, Hadratullah; Sejati, Anang (Indonesian Journal of Islamic Economics and Finance, 2024)
This study aims to analyze the application of the 5C+1S (Character, Capacity, Capital, Collateral, Condition, and Sharia) principles in minimizing the risk of Murabahah financing at Bank Syariah Indonesia KCP Pancor. The research uses a qualitative descriptive approach with primary data through employee and customer interviews and secondary data from bank documents. The results show that the 5C+1S principle helps assess customer eligibility despite obstacles such as limited human resources, lack of selectivity in customer selection, and the influence of economic conditions. To overcome these challenges, intensive training is recommended to improve the quality of human resources, periodic supervision of customers, risk analysis technology, diversification of financing portfolios, and improvement of customer financial literacy. Consistent and adaptive implementation of economic changes can help BSI KCP Pancor mitigate the risk of non-performing financing and maintain the sustainability of its operations.